Ways of perceiving safety: from interpretative registers to mechanisms of interpretation - Noble, Julien (Deviant behavior, 2023)
In the study of fear of crime, perception of safety with respect to the risk of victimization is often viewed as the mere consequence of the absence of perceived risk. This paper takes the opposite view: that it is a complex phenomenon resting on a plurality of interpretative registers. Analysis of some thirty interviews of students at a French university shows three different ways of perceiving safety (fragility, self-confidence and tranquility), each rests on a specific relationship to oneself and toward supposed aggressors. Having shown this, we then look at how these interpretations emerge and evolve over time. Interpretations are by no means attached to individuals, rather, they fluctuate with the situations encountered and with past experiences, whence the importance of bringing out the two dimensions - synchronic and diachronic - of this phenomenon.